Intensive care syndrome [Yoǧun bakim sendromu] - (:unkn) unknown (My University, 2003)
The aim in this literature review is to describe the definitions, clinical signs and symptoms, causative factors, and treatment and nursing care of intensive care syndrome. We found that it is not clear which symptoms should be included in the syndrome, when the syndrome may appear and how many clients may be affected. We also found that syndrome has generally been examined by using a medical and psychological approach, although in the last few years it has also analysed from a nursing perspective. From nursing perspective we can say that the syndrome may be seen as an individual pattern experienced by clients during their stay in an intensive care unit. Its signs and symptoms may be lasts for a shorter or longer period even after discharge from the unit. As a result, ICU syndrome is vicious circle that consists of, and is caused by, a complex interaction between many factor.